2000
DOI: 10.1530/eje.0.1430335
|View full text |Cite
|
Sign up to set email alerts
|

Medullary thyroid carcinoma: an accurate pre-operative diagnosis by reverse transcription-PCR

Abstract: Objective: To study the expression of calcitonin (CT) and thyroglobulin mRNA in samples of leftover cells in needles used for ®ne-needle aspiration biopsy either from thyroid tumours or cervical lymph nodes. Patients and methods: Specimens were analysed using reverse transcription-polymerase chain reaction; 12 samples from 11 patients were included and molecular diagnosis was compared with cytological or histological diagnosis and serum CT measurements. Results: Transcripts of the CT gene were detected in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In 1 study by Arturi et al, in vivo FNA samples from lymph nodes were analyzed by RT‐PCR for the presence of thyroid cancer metastases, and 5 of 46 samples (10.9%) were found to be negative for GAPDH expression 39. In several other studies, all performed on a small sample (3 to 21 FNA samples), no inadequate samples for RT‐PCR were found 20, 40–44. In some studies, the exact number of inadequate samples for RT‐PCR analysis was not explicitly reported 17, 21, 24, 45–49…”
Section: Discussionmentioning
confidence: 99%
“…In 1 study by Arturi et al, in vivo FNA samples from lymph nodes were analyzed by RT‐PCR for the presence of thyroid cancer metastases, and 5 of 46 samples (10.9%) were found to be negative for GAPDH expression 39. In several other studies, all performed on a small sample (3 to 21 FNA samples), no inadequate samples for RT‐PCR were found 20, 40–44. In some studies, the exact number of inadequate samples for RT‐PCR analysis was not explicitly reported 17, 21, 24, 45–49…”
Section: Discussionmentioning
confidence: 99%
“…MTC was preoperatively diagnosed in three patients by molecular detection of these mRNAs, and the diagnoses were confirmed by subsequent cytologic and histopathologic analyses (54). Using identical primer sequences, Bugalho et al (55) studied six patients with MTC and found calcitonin mRNA in samples of leftover cells of FNAB of all these patients, but not of patients with follicular adenoma and follicular/papillary carcinoma, respectively (55). On the other hand, all MTC patients presented with high levels of serum calcitonin, whereas all of the non-MTC patients but one (in which basal calcitonin serum was 10.5 ng/L) had serum calcitonin levels below 10 ng/L.…”
Section: Medullary Thyroid Carcinomamentioning
confidence: 99%
“…In contrast to papillary and follicular thyroid carcinoma, to date only few studies have been published concerning the preoperative diagnosis of medullary thyroid carcinoma using PCR-based methods (53)(54)(55). The reason for that discrepancy may be that patients with MTC are usually readily diagnosed by conventional cytology and serum CT measurements.…”
Section: Medullary Thyroid Carcinomamentioning
confidence: 99%
“…Combined data for the three largest cytopathology series with surgical follow-up indicate that 79% of patients had FNAs that were positive for MTC and 96% suggested some form of thyroid lesion (i.e., an 'indeterminate' nodule) that prompted surgical intervention for diagnosis and/or treatment [2, [40][41][42]. Routine cytological specimens are not usually stained for calcitonin unless there is a suspicion of MTC, although measurement of calcitonin in the fluid aspirate has been demonstrated as a diagnostic tool for the diagnosis of MTC in a thyroid nodule [2, [43][44][45][46][47].…”
Section: Diagnosis Of Mtcmentioning
confidence: 99%